Prestavljanje velikih večbobenskih žičnih žerjavov glede na trajanje spravila lesa ter značilnosti linij - Košir, Boštjan (Gozdarski vestnik, 2014)
We deal with the ratio of the duration of moving large multidrum cable cranes with towers to the duration of wood harvest by the use of large multidrum cable cranes with towers. Into the move we included duration of assembling, dismantling and move as well as duration of smaller repairs occurring during the move. The research encompassed 205 lines of cable yarding with several cable cranes tipe Syncrofalke with cariage - Sherpa U III 3 t produced by MM-Forsttechnik (A) on diverse trucks; some of them were equipped with Konrad Woody 60 processors. Basic data was gathered along with routine evidences of working hours of cable crane operators from forestry companies. Forestry companies keep records of machine and working hours with diverse accuracy, therefore we combined several procedures in assembly and dismantling duration and wood harvest duration. Factors - felling concentration, line length, yarding direction - affecting assembly and dismantling as well as harvest duration were analyzed. The impact of the factors is described analytically and jointly for combinations of categories of yarding line lenght and move duration for the line. Coefficient of assembly and dismantling duration and wood yarding is analyzed in dependence of line length and concentration of wood along the cable line. Shown are total costs of wood harvest depending on the coefficient of move.
Keywords: gozdne žičnice; spravilo lesa; montaža; demontaža; učinki spravila lesa; stroški